Hydrogen gas inhalation improves delayed brain injury by alleviating early brain injury after experimental subarachnoid hemorrhage - Kumagai, Kosuke (Sci Rep, 2020)
Molecular hydrogen (H(2)) protect neurons against reactive oxygen species and ameliorates early brain injury (EBI) after subarachnoid hemorrhage (SAH). This study investigated the effect of H(2) on delayed brain injury (DBI) using the rat SAH + unilateral common carotid artery occlusion (UCCAO) model with the endovascular perforation method. 1.3% H(2) gas (1.3% hydrogen premixed with 30% oxygen and balanced nitrogen) inhalation was performed on days 0 and 1, starting from anesthesia induction and continuing for 2 h on day 0, and starting from anesthesia induction and continuing for 30 min on day 1. EBI was assessed on the basis of brain edema, expression of S100 calcium-binding protein B (S100B), and phosphorylation of C-Jun N-terminal kinase on day 2, and neurological deficits on day 3. Reactive astrogliosis and severity of cerebral vasospasm (CV) were assessed on days 3 and 7. DBI was assessed on the basis of neurological deficits and neuronal cell death on day 7. EBI, reactive astrogliosis, and DBI were ameliorated in the H(2) group compared with the control group. CV showed no significant improvement between the control and H(2) groups. This study demonstrated that H(2) gas inhalation ameliorated DBI by reducing EBI without improving CV in the rat SAH + UCCAO model.